Discover answers to your questions with Westonci.ca, the leading Q&A platform that connects you with knowledgeable experts. Our Q&A platform offers a seamless experience for finding reliable answers from experts in various disciplines. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.
Sagot :
[tex]4x-2y=48\\ \\ 2x+6y=-18[/tex]
First we'll multiply the second equation by -2
[tex]-2\cdot (2x+6y)=-2\cdot -18\\ \\ -4x-12y=36[/tex]
Now let's add the new equation and the first one.
[tex](4x-2y)+(-4x-12y)=48+36\\ \\ 4x-4x-2y-12y=48+36\\ \\ -14y=84\\ \\ y=\frac { 84 }{ -14 } \\ \\ y=-6[/tex]
We found y's value. We'll plug it in one of the equations to find x's value.
[tex]y=-6\\ \\ 4x-2y=48\\ \\ 4x-2\cdot -6=48\\ \\ 4x+12=48\\ \\ 4x=48-12\\ \\ 4x=36\\ \\ x=\frac { 36 }{ 4 } \\ \\ x=9[/tex]
Solution ;
(9, -6)
First we'll multiply the second equation by -2
[tex]-2\cdot (2x+6y)=-2\cdot -18\\ \\ -4x-12y=36[/tex]
Now let's add the new equation and the first one.
[tex](4x-2y)+(-4x-12y)=48+36\\ \\ 4x-4x-2y-12y=48+36\\ \\ -14y=84\\ \\ y=\frac { 84 }{ -14 } \\ \\ y=-6[/tex]
We found y's value. We'll plug it in one of the equations to find x's value.
[tex]y=-6\\ \\ 4x-2y=48\\ \\ 4x-2\cdot -6=48\\ \\ 4x+12=48\\ \\ 4x=48-12\\ \\ 4x=36\\ \\ x=\frac { 36 }{ 4 } \\ \\ x=9[/tex]
Solution ;
(9, -6)
4x - 2y = 48 ⇒ 4x - 2y = 48
2x + 6y = -18 ⇒ 4x + 12y = -36
-14y = 84
-14 -14
y = -6
4x - 2(-6) = 48
4x + 12 = 48
- 12 - 12
4x = 36
4 4
x = 9
(x, y) = (9, -6)
2x + 6y = -18 ⇒ 4x + 12y = -36
-14y = 84
-14 -14
y = -6
4x - 2(-6) = 48
4x + 12 = 48
- 12 - 12
4x = 36
4 4
x = 9
(x, y) = (9, -6)
We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. Thank you for visiting Westonci.ca, your go-to source for reliable answers. Come back soon for more expert insights.